Transcriptomic analysis of patients with immune thrombocytopenia treated with eltrombopag. (16th November 2020) - Hernández-Sánchez, Jesús María; Bastida, José María; Alonso-López, Diego; Benito, Rocío; González-Porras, José Ramón; De Las Rivas, Javier; Hernández Rivas, Jesús María; Rodríguez-Vicente, Ana Eugenia
Abstract: In the last years, the use of thrombopoietin receptor agonists (TPO-RA), eltrombopag and romiplostim, has improved the management of immune thrombocytopenia (ITP). Moreover, eltrombopag is also active in patients with aplastic anemia and myelodysplastic syndrome. However, their mechanisms of action and signaling pathways still remain controversial. In order to gain insight into the mechanisms underlying eltrombopag therapy, a gene expression profile (GEP) analysis in patients treated with this drug was carried out. Fourteen patients with chronic ITP were studied by means of microarrays before and during eltrombopag treatment. Median age was 78 years (range, 35–87 years); median baseline platelet count was 14 × 10 9 /L (range, 2–68 × 10 9 /L). Ten patients responded to the therapy, two cases relapsed after an initial response and the remaining two were refractory to the therapy. Eltrombopag induced relevant changes in the hematopoiesis, platelet activation and degranulation, as well as in megakaryocyte differentiation, with overexpression of some transcription factors and the genes PPBP, ITGB3, ITGA2B, F13A1, F13A1, MYL9 and ITGA2B . In addition, GP1BA, PF4, ITGA2B, MYL9, HIST1H4H and HIST1H2BH, genes regulated by RUNX1 were also significantly enriched after eltrombopag therapy. Furthermore, in non-responder patients, an overexpression of Bcl-X gene and genes involved in erythropoiesis, such as SLC4A1 and SLC25A39, was also observed. To conclude, overexpression in genes involved in megakaryopoiesis, platelet adhesion, degranulation and aggregation was observed in patients treated with eltrombopag. Moreover, an important role regarding heme metabolism was also present in non-responder patients.